Weaning Failure in Mechanical Ventilation: a Literature Review - Sakti, Pradhika Perdana; Anjarwani, Setyasih (Heart Science Journal, 2023)
Mechanical ventilation is a method of ventilation support through positive pressure breath application. It is used in cases of ventilation and/ or oxygenation failure. Due to its related complications mechanical ventilation should be withdrawn from the patient as soon as possible, called a weaning process. The result of the weaning of mechanical ventilation determines the patient’s prognosis. Patient will go through several assessments before a weaning decision is made. Subsequently, patient will be placed on an unconstrained breathing test (SBT) to check whether the patient's respiratory muscle is equipped for accepting its work of relaxing. Weaning disappointment is characterized as disappointment on SBT or reintubation at 48 hours following extubation. Several factors related to weaning failure are increasing airflow resistance, decreasing compliance, respiratory muscle fatigue, and the patient’s underlying conditions. Techniques to conquer these variables are expected to lessen the pace of disappointment of the weaning system.